Jual Beli yang Diridhoi dalam Perspektif Surat An-Nisa’ (4) Ayat 29 - Cipta, Hendra (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2018)
Al-Qur'an as the main reference guide for the life of believers has set a reference in terms of worship and muamalah. In the field of muamalah, al-Qur'an also pays attention that this worldly affair is also valuable as worship by not violating sharia rules. One that relates to this is the Qur'anic guidance on ethics in the sale and purchase transactions contained in the An-Nisa letter (4) verse 29 which emphasizes that every believer must obtain assets in a way that is justified by sharia, one of the characteristics of things this is the passion between the seller and the buyer in the sale and purchase transaction.